How do people interpret macroeconomic shocks? Evidence from U.S. survey data - Martin Geiger; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
We study the revision of survey expectations in response to macroeconomic shocks, which we identify in vector autoregressive models with sign restrictions. We find that survey respondents distinguish between movements along the Phillips curve and shifts of the Phillips curve, depending on the type of the shock that hits the economy. In addition, expectations about future interest rate dynamics are revised broadly in line with a Taylor rule. While the macroeconomic shocks account only for a small share of the forecast error variance of survey measures elicited from consumers, they are more relevant for the expectations of professional forecasters. This result is consistent with models of rational inattention.
Keywords: E00; E32; D84; 330; Macroeconomic Expectations; Michigan Survey; Structural Vector Autoregression; Zero and Sign Restrictions